The restrictions on travel of elderly tourists and their mitigation by facilitators and negotiation strategies - Lopes, Maria Carlos (2020)
The segment of the elderly population has taken on a heterogeneous character due to the various economic and social policies and reforms that have been implemented by the governments of the various countries. This is the baby-boom generation, that is, individuals who were born between 1946 and 1964, and who currently have greater purchasing power than previous generations and have a high interest in leisure moments where travel ends up having great meaning. However, about half of the population is affected by several factors, which prevent travel. In this sense, the objective of this work aims to investigate how, in the literature review, travel constraints are mitigated or eliminated through facilitators or negotiation strategies. Tourism promoters and managers, stakeholders and DMO’s, have, thus, the great challenge of mitigating, as much as possible, the travel restrictions of elderly tourists, through several strategies and tools that allow a greater participation of this segment of the population in tourism activities.